2016
DOI: 10.1128/iai.00432-16
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Inoculation with Chlamydia muridarum Leads to a Long-Lasting Infection Restricted to the Gastrointestinal Tract

Abstract: cChlamydia has been detected in the gastrointestinal tracts of both animals and humans. However, it remains unclear whether the chlamydial organisms can be introduced into the gastrointestinal tract via pathways independent of the oral and anal routes. We have recently shown that Chlamydia muridarum spreads from the genital tract to the gastrointestinal tract potentially via the circulatory system. To test whether hematogenous C. muridarum can spread to and establish a long-lasting colonization in the mouse ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 48 publications
3
52
0
3
Order By: Relevance
“…For intragastric inoculation, EBs diluted in 100 l of SPG that contained 2 ϫ 10 5 IFU or the desired number of IFU as indicated for individual experiments were delivered to the stomach using a straight-balled end needle designed for mouse oral gavage (N-PK 020; Braintree Scientific Inc., Braintree, MA). Following the initial inoculation, both vaginal and rectal swabs were taken periodically or organs/tissues were harvested (after mice were sacrificed) for titration of viable organisms as described previously (20,21,26). In some experiments, mice were treated with an anti-CD4 antibody, while in others, exogenous molecules or donor T cells were provided as described below.…”
Section: Methodsmentioning
confidence: 99%
“…For intragastric inoculation, EBs diluted in 100 l of SPG that contained 2 ϫ 10 5 IFU or the desired number of IFU as indicated for individual experiments were delivered to the stomach using a straight-balled end needle designed for mouse oral gavage (N-PK 020; Braintree Scientific Inc., Braintree, MA). Following the initial inoculation, both vaginal and rectal swabs were taken periodically or organs/tissues were harvested (after mice were sacrificed) for titration of viable organisms as described previously (20,21,26). In some experiments, mice were treated with an anti-CD4 antibody, while in others, exogenous molecules or donor T cells were provided as described below.…”
Section: Methodsmentioning
confidence: 99%
“…Although chlamydial organisms have been detected in the GI tracts of both human and animal hosts (26-28, 30, 31, 33-44) and C. muridarum is known to colonize the GI tract for long periods of time (26,(30)(31)(32)(33), the medical significance of these phenomena remains unclear. Here, we present the first experimental evidence of a correlation of C. muridarum spreading to and colonization of the GI tract with its pathogenicity in the upper genital tract.…”
Section: Discussionmentioning
confidence: 99%
“…The organs and tissue segments were homogenized in cold SPG buffer. Live C. muridarum organisms released into swab suspensions or tissue supernatants were titrated on HeLa cells in duplicate as described previously (6,19,20,26,31,32). The total number of IFUs per swab or tissue sample was converted into log 10 for calculation of the mean and standard deviation across mice in the same group at each time point.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed that long lasting C. muridarum colonization of the murine gastrointestinal (GI) tract can be established with very low inocula administered orally 137. Intravenous inoculation with a bioluminescent derivative of C. muridarum also resulted in GI colonization 138, revealing a systemic route to this mucosal site. Treatment with doxycycline cleared GI infection but azithromycin treatment was ineffective 139.…”
Section: Treatment and Preventionmentioning
confidence: 99%